2019
DOI: 10.3390/su11051463
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Job Control, SOC Strategies, and Age in Sustaining Work Ability in a Sample of Administrative Employees

Abstract: In recent years, the average age of workers has risen. Because of that, work ability is reducing in many sectors, especially in a public context. Given the above, it is necessary to investigate the individual and organisational resources that can play a role in the protection of work ability. This study investigates the work ability of administrative workers, examines selection, optimisation, and compensation (SOC) as a form of mediation between job control and work ability, and explores the relationship of jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…According to Kahana and Kahana model, preventive strategies are applied to reduce threats, to avoid negative consequences and control change (Kahana & Kahana, 2001). It is consistent with the preventive strategies of the SOC model that seek to acquire resources for achieving life goals (Sottimano, Guidetti, Viotti, & Converso, 2019). These behaviors represent conscious selection and are influenced by social factors (Brojeni, Ilali, Taraghi, & Mousavinasab, 2019;Monfared et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…According to Kahana and Kahana model, preventive strategies are applied to reduce threats, to avoid negative consequences and control change (Kahana & Kahana, 2001). It is consistent with the preventive strategies of the SOC model that seek to acquire resources for achieving life goals (Sottimano, Guidetti, Viotti, & Converso, 2019). These behaviors represent conscious selection and are influenced by social factors (Brojeni, Ilali, Taraghi, & Mousavinasab, 2019;Monfared et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings were consistent with SOC theory and COR theory. When old employees effectively used limited personal resources through SOC, they could still complete the job requirements [33]. Moreover, employees with more resources at work were more capable of using their own coping strategies to maximize work-related resources and create favorable working conditions for individuals [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Radhakrishnan [17] reviewed 19 articles on the use and effect of SOC in patients with chronic diseases and found that SOC can improve symptoms and bring about subjective well-being. In addition, researchers have proved that using SOC strategies predicts well-being [33]. Despite the decline in physical function, the elderly who operated at a high SOC had a higher well-being, while the elderly with a low SOC had a lower well-being despite higher physical function [13].…”
Section: Soc Strategies and Well-beingmentioning
confidence: 99%
See 2 more Smart Citations